Nested Optimization for the Synthesis of Asymmetric Shaped Beam Patterns in Subarrayed Linear Antenna Arrays - Rocca, Paolo; Poli, Lorenzo; Anselmi, Nicola; Massa, Andrea (IEEE transactions on antennas and propagation, 2022)
In this article, a novel clustering method for synthesizing asymmetric shaped beam patterns in subarrayed linear antenna arrays is presented. The definition of the elements aggregations along with the corresponding weighting coefficients is accomplished through two nested iterative loops. An external loop is aimed at determining the optimal excitations of a reference fully populated array that fits user-defined pattern masks, while the internal one is devoted to the synthesis of the best subarrayed layout affording the closest pattern to the reference one by means of a {k} -means-based algorithm that minimizes the total intracluster variations. Representative numerical results are presented and compared with competitive state-of-the-art solutions to assess the effectiveness of the proposed synthesis method.